2002
DOI: 10.1055/s-2002-35834
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Endoscopic Sphincterotomy: Results From a Single Tertiary Referral Center

Abstract: In this single-center series, we found a complication rate of ES in about 7 %, comparable to that in multicenter series. Precut papillotomy and sphincter of Oddi dysfunction were the main independent risk factors for ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 19 publications
7
68
1
3
Order By: Relevance
“…Over all complication rate was 4.9% in the study by Masci E et al and 11.2% in the study by Vandervoort J et al 10,11 The incidence of post ERCP pancreatitis, in a metaanalysis of 21 prospective studies, was approximately 3.5% but ranged widely (1.6-15.7%) depending on patient selection. [5][6][7] Vandervoort J et al, reported acute pancreatitis in 7.2% of patients undergoing therapeutic ERCP. 11 In the present study post ERCP pancreatitis developed in 5% patients which is comparable to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over all complication rate was 4.9% in the study by Masci E et al and 11.2% in the study by Vandervoort J et al 10,11 The incidence of post ERCP pancreatitis, in a metaanalysis of 21 prospective studies, was approximately 3.5% but ranged widely (1.6-15.7%) depending on patient selection. [5][6][7] Vandervoort J et al, reported acute pancreatitis in 7.2% of patients undergoing therapeutic ERCP. 11 In the present study post ERCP pancreatitis developed in 5% patients which is comparable to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of post ERCP pancreatitis ranges from 1.6% to 15.7%, depending on patient selection. 5,6 Haemorrhage is primarily a complication related to sphincterotomy. Haemorrhagic complications may be immediate or delayed, with recognition occurring up to 2 weeks after the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…10 There is wide disparity but the most accurate overall risk of PEP from prospective studies ranges from 3%-10%. 1,4,5,[11][12][13][14][15][16] A survey of prospective studies in 2007 reported that about 10% of PEP cases were graded as severe and the overall mortality of PEP was 3%. 1 …”
Section: Post-ercp Pancreatitismentioning
confidence: 99%
“…However the criteria for what was considered reportable event was not consistent across all studies. 4,11 What further complicates the picture is that rates of insignificant or 'trickle' bleeding range up to 30%-69% after sphincterotomy. 146,147 Also, the threshold for clinical significance varies including criteria such as duration (# of minutes) of ongoing blood loss, need for blood transfusion, hospitalization, and secondary therapeutic intervention (endoscopic, angiographic, etc.).…”
Section: Bleedingmentioning
confidence: 99%
See 1 more Smart Citation